Menelusuri Sejarah, Nilai Islam dan Sosial Budaya Wayang Kulit dalam Pertunjukan Wayang Kulit - Suhadah, Suhadah; Khotimah, Husnul; Dwi Wulandari, Enza; Adawiyyah, Rabiatul; Andika, Angga; Suswandi , Suswandi; Fahdil, Fahdil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore the history, Islamic values, and socio-cultural aspects of the Lombok shadow puppet show. This research method uses a qualitative approach with ethnographic methods, data collected through participant observation, in-depth interviews with puppeteers and community leaders, and documentation studies. The results of the study indicate that Lombok shadow puppets are influenced by Javanese and Balinese culture, but have been adapted to reflect the local identity of the Sasak people. Malat shadow puppets, as one of its types, contain Islamic values ​​such as monotheism, noble morals, and the concept of jihad combined with local culture. This performance also reflects the socio-cultural aspects of the Lombok people, such as belief systems, moral values, social structures, and local traditions. Lombok shadow puppets not only function as entertainment, but also as a medium for preaching and preserving oral traditions. The conclusion shows that Lombok shadow puppets are the result of cultural acculturation that strengthens the identity of the Sasak people and plays an important role in preserving local cultural heritage. Keywords: Acculturation, Lombok Shadow Puppets, Preaching, Islamic Values, Socio-Culture